2010
DOI: 10.1038/sj.bjc.6605949
|View full text |Cite
|
Sign up to set email alerts
|

A 50% higher prevalence of life-shortening chronic conditions among cancer patients with low socioeconomic status

Abstract: Background:Comorbidity and socioeconomic status (SES) may be related among cancer patients.Method:Population-based cancer registry study among 72 153 patients diagnosed during 1997–2006.Results:Low SES patients had 50% higher risk of serious comorbidity than those with high SES. Prevalence was increased for each cancer site. Low SES cancer patients had significantly higher risk of also having cardiovascular disease, chronic obstructive pulmonary diseases, diabetes mellitus, cerebrovascular disease, tuberculosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 39 publications
5
103
3
Order By: Relevance
“…Differences in the uptake of screening, 22 stage at diagnosis, 3 level of comorbidity 23,24 and access to optimal treatment 25 are all potential explanations for the difference in cancer survival between rich and poor patients. Whilst differences in stage at diagnosis and comorbidity have explained only a small proportion of the socioeconomic disparities in survival from colorectal cancer, 26 differential access to healthcare has been shown to strongly influence these inequalities in survival.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the uptake of screening, 22 stage at diagnosis, 3 level of comorbidity 23,24 and access to optimal treatment 25 are all potential explanations for the difference in cancer survival between rich and poor patients. Whilst differences in stage at diagnosis and comorbidity have explained only a small proportion of the socioeconomic disparities in survival from colorectal cancer, 26 differential access to healthcare has been shown to strongly influence these inequalities in survival.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolating, this may indicate that differences between SES classes in lifestyle and access to care have been unchanged in patients with CRC over time. 29 Frederiksen et al 13 studied the role of SES in postoperative mortality after elective CRC surgery in a Danish cohort and found that low SES patients had an excess risk of death, which was mostly accounted for by comorbidity and lifestyle characteristics. The association of a low SES and a high prevalence of (multi) morbidity is also evident in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Cancers in less-advantaged women might be diagnosed at a more advanced stage because of low screening uptake, delay in seeking health care, and poor access to specialist care (5,6). Furthermore, women with a lower socioeconomic position tend to have more comorbid conditions, which has also been associated with survival from cancer (4,7). This might either increase surveillance or, conversely, decrease individual resources, the attention to abnormal gynecologic symptoms and cause delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%